2023
DOI: 10.1021/acsmaterialslett.3c00740
|View full text |Cite
|
Sign up to set email alerts
|

The Structure Determination of Organic Molecules by Co-crystallization of Anthracene-Based Crystallization Chaperone

Heng Li,
Jianmin Jiao,
Wang Xie
et al.

Abstract: Single crystal X-ray diffraction is considered to be a highly reliable method for determining the molecular structures and absolute conformation at the atomic level, but this technique is limited to the application of oily organic molecules that are difficult to crystallize. Here, we report an anthracene-based crystallization chaperone TMAPA to overcome the above limitation, where 56 various oily organic guest molecules were cocrystallized with TMAPA in the organic solvent. As a result, 51 high-resolution co-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…In the absence of such functional groups, and their strong intermolecular forces directing the solid-state packing of these co-crystallisations, methodologies have instead shifted to trapping the liquid substrates within cavities or inside porous networks. 29,[32][33][34][35][36] These methodologies are impressive in the scope of their substrates successfully co-crystallised, especially for substrates that lack any readily-exploited functional groups (e.g., alkanes). 33 However, the required porosity of such networks can result in large unit cells comprised of primarily light-atom molecules (Z < Si) can act as double-edged swords, given that such systems can necessitate the use of powerful synchrotron radiation sources.…”
Section: Catch-and-release Agentmentioning
confidence: 99%
“…In the absence of such functional groups, and their strong intermolecular forces directing the solid-state packing of these co-crystallisations, methodologies have instead shifted to trapping the liquid substrates within cavities or inside porous networks. 29,[32][33][34][35][36] These methodologies are impressive in the scope of their substrates successfully co-crystallised, especially for substrates that lack any readily-exploited functional groups (e.g., alkanes). 33 However, the required porosity of such networks can result in large unit cells comprised of primarily light-atom molecules (Z < Si) can act as double-edged swords, given that such systems can necessitate the use of powerful synchrotron radiation sources.…”
Section: Catch-and-release Agentmentioning
confidence: 99%
“…17,19,21 Subsequently, other research groups reported the use of GS frameworks for structure determination of target molecules, 23,24 and very recently, a report in this journal described an anthracene-modified adamantoid molecular chaperone for structure determination of guests. 25 Over the past three decades, our laboratory has reported a substantial number of molecular host frameworks, built from two-dimensional hydrogen-bonded networks of guanidinium (G) and organosulfonate (S) ions (Figure 1), capable of encapsulating a wide range of guests and determining their molecular structure. 26−30 These frameworks can adopt various architectures and pucker about hydrogen-bonding "hinges" in response to the steric demands of a target guest, enabling inclusion of a wide range of guests having various sizes and shapes in stoichiometric amounts.…”
mentioning
confidence: 99%
“…“molecular chaperones”, were employed as hosts for the determination of molecular structure, including absolute configuration, for a variety of guest molecules. This method involved adding one of three different adamantoid chaperones (Figure S33) to a neat guest, in liquid form, at room temperature, heating the mixture to achieve a homogeneous solution, followed by cooling with the aim of producing a cocrystal of the adamantoid chaperone and guest. ,, Subsequently, other research groups reported the use of GS frameworks for structure determination of target molecules, , and very recently, a report in this journal described an anthracene-modified adamantoid molecular chaperone for structure determination of guests …”
mentioning
confidence: 99%
See 2 more Smart Citations